Unusual Sound Sources - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Three distinct approaches to creating unusual music are explored. - - Take a trip to Bainbridge Island to discover a harp that plays only when the wind blows - - See how, through technology, animals can produce sounds that become the source for a musical composition - - Visit a junkyard with the Metaphonics and see how they work the sound properties of ordinary pieces of metal and wood into a most unusual performance.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - I. The Wind Harp of Bainbridge Island - - Vocabulary - - Student Follow-up - - II. Electronic Digital Sound Sampling - - Vocabulary - - III. Metaphonics (Sounds from the Junkyard) - - Student Follow-up - - Correlations with THE MUSIC CONNECTION - -About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Musical instruments; Sound - - Recording and reproducing; Films for the hearing impaired